Orquestra Errante: Free Improvisation and Decolonial Practices at the Brazilian University - Costa, Rogerio Luiz Moraes (Critical Studies in Improvisation / Études critiques en improvisation, 2025)
Through this article, I seek to demonstrate how much the activities developed by Orquestra Errante for more than ten years at the University of São Paulo were consolidated as a practical and theoretical proposal for reflection on issues related to new decolonial epistemologies. These decolonial perspectives emerge as a fundamental theme for the urgent review of political pedagogical projects at universities that can help and enable the confrontation of colonial cultural dependence and economic exclusion and inequality in Brazil.